Effect of growing conditions and postharvest processing on arabica coffee bean physical quality features and defects. Issue 4 (April 2022) - Worku, Mohammed; Astatkie, Tessema; Boeckx, Pascal
Abstract: The individual and interaction effects of elevation, production system (PS), shade and postharvest processing (PHP) on the ratio of dry beans to red cherries and the green bean physical quality features and defects of arabica coffee in southwestern Ethiopia were evaluated. The results showed that, with increasing elevation, the proportions of the total defected beans and large beans decreased while that of medium beans increased. Moreover, the proportion of secondary defects, 1000 seed weight and bean volume were higher for lowland and midland coffees than for highland coffee, but bean density was higher for highland than for lowland and midland coffees. The proportion of the total defected beans was also higher for modern plantation coffee in lowland than for modern plantation and semi-plantation coffees in midland and highland, but the 1000 seed weight was lower for semi-plantation coffee in highland than for modern plantation coffee in lowland and midland. The ratio of primary and secondary defects respectively was higher for dry- and wet-processed coffee in lowland than for dry- and wet-processed coffees in midland and highland. But, the ratio of small beans was lower for wet-processed coffee in lowland than for dry-processed coffee across elevations. The ratio of dry beans to red cherries and the 100 beans volume were higher for wet-processed modern plantation and semi-plantation coffees in midland than for dry-processed coffees of both production systems across elevations. However, the ratio of large beans was higher (1) for wet-processed modern plantation coffee in lowland than for dry- and wet-processed coffees of both production systems across elevations, and (2) for coffee that was grown without shade and wet-processed in lowland than for other coffees. Bean density was higher for dry-processed modern plantation and semi-plantation coffee in midland and highland, respectively than for other coffees across elevations. Overall, these results underlined the primary effects of elevation and PS, and the complex interaction effects between PHP and PS or shade on the ratio of dry beans to red cherries and the physical features and defects of green arabica coffee beans. Highlights: Coffee bean physical features and defects were mainly affected by elevation. Production system also affected coffee bean physical features and defects. Production system effect on dry beans to red cherries ratio and bean physical features depended on postharvest processing. Shade effect on the proportion of large beans depended on the postharvest processing. Abstract : Elevation, Coffee shade, Coffee production system, Arabica coffee, Dry beans to red cherries ratio, Bean physical features, Defective beans, Southwestern Ethiopia.